A warrior's heart [large type] - Beller, Misty M. (Beller, Misty M. Brides of Laurent, 2021)
"On assignment to help America win the War of 1812, Evan MacManus is taken prisoner by Brielle Durand-the key defender of her people's secret French settlement in the Canadian Rocky Mountains. But when his mission becomes at odds with his growing appreciation of Brielle and the villagers, does he dare take a risk on the path his heart tells him is right?"-"--